The heavy metal genre in an Islamic city of Padang: struggle and promotion - Endrizal Ridwan; Bardi Rahmawan (IAIN Salatiga, 2021)
A qualitative research was conducted on how heavy metal survived and competed with other genres in a sacred city of Padang Indonesia, where metal and religion seemed to be unmatched. This research aims at understanding why heavy metal showed no significant progress despite its long existence in the city. An interview of five musicians from the five most popular metal bands in the city revealed that the metal music genre had struggled to survive for two reasons: the stigma of its negative influence on society and the failure of metal musicians in proving that metal symbols and lifestyle were irrelevant to the arts of metals. A SWOT analysis suggests that the metalheads need to utilize their subcultural capital by modifying their music using religious lyrics within the scene and by following social norms outside the scene.